2006
DOI: 10.1210/en.2005-0791
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Leptin in the Development of the Cerebral Cortex in Mouse Embryos

Abstract: Leptin is detected in the sera, and leptin receptors are expressed in the cerebrum of mouse embryos, suggesting that leptin plays a role in cerebral development. Compared with the wild type, leptin-deficient (ob/ob) mice had fewer cells at embryonic day (E) 16 and E18 and had fewer 5-bromo-2'-deoxyuridine(+) cells at E14 and E16 in the neuroepithelium. Intracerebroventricular leptin injection in E14 ob/ob embryos increased the number of neuroepithelium cells at E16. In cultured neurosphere cells, leptin treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 66 publications
2
69
0
2
Order By: Relevance
“…Indeed, leptin has been found to act as an anti-apoptotic hormone under stress conditions (Russo et al, 2004). A role for leptin in neurogenesis and neurodevelopment is strengthened by the observations of Udagaw and others (Udagawa et al, 2006) that leptin stimulates the proliferation of precursor cells committed to neuronal differentiation, and promotes neuronal terminal differentiation. Recent work by Guo et al (2007) suggests that leptin serves a neurotrophic function in the developing and adult hippocampus by enhancing mitochondrial resistance to apoptosis and excitoxicity.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, leptin has been found to act as an anti-apoptotic hormone under stress conditions (Russo et al, 2004). A role for leptin in neurogenesis and neurodevelopment is strengthened by the observations of Udagaw and others (Udagawa et al, 2006) that leptin stimulates the proliferation of precursor cells committed to neuronal differentiation, and promotes neuronal terminal differentiation. Recent work by Guo et al (2007) suggests that leptin serves a neurotrophic function in the developing and adult hippocampus by enhancing mitochondrial resistance to apoptosis and excitoxicity.…”
Section: Discussionmentioning
confidence: 95%
“…The association between fasting plasma leptin concentrations and reduced GM volumes of some cortical (i.e., inferior frontal operculum and postcentral gyrus) and striatal (i.e., putamen) areas may be unexpected, given the reported neurotrophic action of leptin on the brains of ob/ ob mice [23][24][25]. These mice, however, have complete leptin deficiency [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…These mice, however, have complete leptin deficiency [23][24][25]. It is not known if the neurotrophic effects of leptin on mice with leptin deficiency are relevant to the neuronal effects of leptin in lean or obese persons, who have normal or high leptin concentrations, respectively [9].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that leptin maintains neuronal stem cells and progenitor cells and is related to neuronal and glial development in the mouse embryonic brain (Udagawa et al 2006a;Udagawa et al 2006b), suggesting that leptin plays an important role in embryonic cerebrocortical development. It is also reported that factors expressed during the developmental stage of the CNS exhibits an overexpression pattern by neoplastic cells in mature brain (Merrill and Oldfield 2005;Plata-Salaman 1991;Trojan et al 2007).…”
Section: Leptin Increases the Migration And Invasion Of C6 Glioma Cellsmentioning
confidence: 99%